The role of experts in the Covid-19 pandemic and the limits of their epistemic authority in democracy - Lavazza, Andrea; Farina, Mirko (New Zealand Science Review, 2022)
Copyright © 2020 Lavazza and Farina. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY). It was originally published in Frontiers in Public Health, 14 July 2020 | Volume 8 | Article 356 (https:// doi.org/10.3389/fpubh.2020.00356) and is published here with permission.